Level of knowledge among pharmacists regarding anaphylaxis and the use of epinephrine autoinjectors. (23rd October 2018) - Worm, Margitta; Molaie, Novin; Dölle, Sabine
Summary: Background: Epinephrine autoinjectors for intramuscular administration are the treatment of choice for self‐medicating severe allergic reactions. Data from the anaphylaxis registry shows that patients rarely use their epinephrine pens. Pharmacists play a key role as liaison between prescribers and patients. Patients and methods: Using a standardized questionnaire, the objective of the present study was to assess the level of knowledge among pharmacists regarding anaphylaxis and its treatment. Data derived from 213 pharmacists was included in the study. Results: Our data reveals that pharmacists consider anaphylaxis to be a disorder that is associated with an impairment in quality of life. The most common triggers of anaphylaxis according to pharmacists (insect venom, foods, and drugs) correspond to those listed in the anaphylaxis registry. Based on the survey, pharmacists readily recognize anaphylactic reactions from case descriptions. However, there are still knowledge deficits with respect to the management of anaphylaxis and current guidelines. Conclusions: Our findings suggest that the level of knowledge among pharmacists with regard to anaphylaxis warrants improvement. As this professional group plays a crucial part in the care of patients with allergic disorders, future measures should be aimed at strengthening this role by raising awareness and introducing training modules.